THE EFFECT OF TAX SANCTIONS AND TAX AUTHORITIES SERVICES ON TAX COMPLIANCE AND TAXPAYER AWARENESS AS MODERATION VARIABLE (SURVEY ON CORPORATE TAXPAYERS DOMICILED IN TANGERANG) - Kurniawan, Irwan; Daito, Apollo (Dinasti International Journal of Management Science, 2021)
This research examines the Effect of Tax Sanctions and Tax Authorities Service on Tax Compliance Taxpayer Awareness as Moderation Variables. The population in this study is corporate taxpayers who live in Tangerang, based on data until the end of 2018 there were 1,570 taxpayers, the determination of the number of samples was determined using the Slovin formula so that the sample used was 94 respondents. Data were collected using a questionnaire and using the Ordinal scale. The distribution and collection of questionnaires was carried out in June 2020 and the number of questionnaires that could be used was 88 questionnaires or 93%.In analyzing the data used a quantitative approach through Software SPSS 23. The simultaneous Tax Sanction, Tax Authorities Service have a significant effect on Tax Compliance Taxpayer Awareness . Partially Tax sanctions have a significant effect on compliance with corporate taxpayers, the Tax Authorities Service have a significant effect on compliance with corporate taxpayers. Interactionlly awareness of taxpayers moderating tax sanctions does not affect the compliance of corporate taxpayers, awareness of taxpayers moderating tax authorities services have a significant effect on compliance with corporate taxpayers.